Leveraging amino acid sensors as therapeutic targets for tauopathies and related dementias: Molecular and cell biology: Tau‐related mechanisms. (7th December 2020) - Lee, Daniel C.; Ma, Chao; Morgan, Dave; Liang, Huimin; Kovalenko, Andrii; Sandusky‐Beltran, Leslie A.; Calahatian, John Ivan; Kallupurackal, Mani; Hunt, Jerry B; Pandey, Shalini; Blazier, Danielle; Bickford, Paula; et al.
Abstract: Background: Tauopathies including Alzheimer's disease (AD) comprise of over 27 neurodegenerative diseases. Our group has uncovered a unique interaction between uncoupling of amino acid sensors and tauopathies. L‐Arginine metabolism impacts multiple processes that seemingly show considerable influence upon tau biology. Several protein sensors have been identified that sense arginine within the lysosomal lumen, cytoplasm and signal to the mechanistic target of rapamycin complex 1 (mTORC1). GPRC6a, g‐protein coupled receptor also senses arginine levels but also signals to mTORC1. We posit that GPRC6a remains tonically active through extracellular arginine. GPRC6a signaling increases during tauopathies and thereby promotes hyper‐mTORC1 activation and impairs autophagy flux. Method: We performed PCR‐array analysis, biochemical analysis for gene transcripts and protein expression for Alzheimer's disease brain tissue and aged matched controls. We performed a series of mechanistic studies on GPRC6a and tau biology using siRNA, shRNA, drug pharmacology in cell culture models and (PS19 tau mice) or wild‐type littermates. RNA seq was performed on GPRC6a knockout mice crossed with PS19 mice. Result: Our work indicates dysregulation of gene transcripts for arginine sensors, components of mTORC1 signaling in Alzheimer's disease (AD) brains and mice with tauopathy. AD brains and tau PS19 mice showed increased GPRC6a, CASTOR1 and SLC38A9 signifying dysfunction in arginine sensing. Tau PS19 mice showed increased total and extracellular arginine in the brain, which further increased with neuronal activity. GPRC6a gene repression or novel allosteric antagonists decreased mTORC1 activation and reduced tau burden. Conversely, GPRC6a overexpression increased mTORC1 and tau accumulation. Knockout mice for GPRC6a crossed with PS19 tau transgenic mice reversed tau‐induced mRNA signatures in the brain via RNA seq. Microglia and neurometabolism were most affected in GPRC6a knockout mice signifying a critical role for arginine sensors in microglia during tau deposition. Importantly, novel allosteric antagonists to GPRC6a increased microglia phagocytosis and index. Conclusion: Our work identifies a new pathway activated in AD and models of tauopathy yet provides the discovery of a new class of agents that govern microglia function, autophagy and neurometabolism. These data provide new therapeutic strategies for proteinopathies that exploit nutrient sensing dysfunction in AD.